Pharmacological Profile of AS-9705, a Novel Benzotriazolecarboxamide Derivative, as a Gastroprokinetic Agent with Potent Anti-emetic Activity - Yoshikawa, Takashi; Mine, Yukiko; Morikage, Kazuo; Yoshida, Naoyuki (Arzneimittelforschung, 2003)
The pharmacological profile of AS-9705 ((R)-N-(1-ethyl-1H-hexahydroazepin-3-yl)-6-methoxy-1H-benzotriazole-5-carboxamide fumarate monohydrate, CAS 219622-61-4), a novel gastroprokinetic agent with potent anti-emetic activity, was investigated in the present study. AS 9705 inhibited [3H]spiperone binding to human dopamine D2.long receptors, and [3H]R(+)-7-OH-DPAT binding to human dopamine D3 receptors (IC50 values of 58.5 ± 14.0 and 60.8 ± 7.8 (nmol/l), respectively) and had negligible affinity (IC50 > 10 µmol/l) for other neurotransmitter recognition sites examined. Moreover, in ferrets or dogs, AS-9705 dose-dependently inhibited emesis induced by R(+)-7-OH-DPAT and apomorphine with ID50 values of 0.05 mg/kg p.o. and 0.04 mg/kg p.o., respectively. AS 9705 dose-dependently enhanced normal gastric emptying and potently inhibited the delay in gastric empting induced by apomorphine, morphine, cisplatin, clonidine and cholecystokinin in rats. Furthermore, in conscious fasting dogs, AS-9705 dose-dependently stimulated gastric motility. In conclusion, AS-9705 is a novel gastroprokinetic agent with potent antiemetic activity and minimal CNS adverse effects and is, therefore, worthy of clinical investigation.
Keywords: Anti-emetic; AS-9705, anti-emetic effect, dog, ferret, pharmacological profile; CAS 219622-61-4; (R)-N-(1-Ethyl-1H-hexahydroazepin-3-yl)-6-methoxy-1H-benzotriazole-5-carboxamide; fumarate monohydrate; Gastroprokinetic agent